THE EFFECT OF INDEPENDENT COMMISSIONERS, AUDIT COMMITTEES AND FINANCIAL DISTRESS ON THE INTEGRITY OF FINANCIAL STATEMENTS - Dwi Fitrianingsih; Luguh Novantari; Abdurrohman Abdurrohman; Anis Fuad Salam; Fidziah Fidziah (Jurnal Ekonomi, 2023)
This study aims to determine the Influence of Commissioners Independent, Audit Committee, and Financial Distress to Report Integrity On Mining Companies Listed on the Indonesia Stock Exchange (IDX) Period 2017-2021. This research uses a statistical analysis type of research Descriptive with a quantitative approach. The data used is in the form of data Secondary taken indirectly from the company. Technique Sampling is by purposive sampling, where the sampling is taken Samples are carried out on certain considerations as well as criteria. The study Performed using panel data regression with the help of programs Computer Eviews version 9. The results of this study show that partially the commissioner Independent and audit committees have a significant effect on the integrity of reports Finance. And for financial distress the result has no effect on Integrity of financial statements. While simultaneously, independent commissioners, Audit committee, and financial distress together have a significant effect To the integrity of financial statements.